PSILOCYBIN AS AN ADJUNCTIVE TREATMENT FOR DEPRESSION AND PSYCHOLOGICAL DISTRESS IN ONCOLOGY: CURRENT EVIDENCE AND CLINICAL IMPLICATIONS - Komarczewska, Anna; Kociński, Michał; Iglewski, Patryk; Pietrasz, Michał; Idziński, Jakub; Lubomska, Anna (International Journal of Innovative Technologies in Social Science, 2026)
Depression and psychological distress are highly prevalent among patients with cancer and are associated with impaired quality of life, reduced treatment adherence, and poorer clinical outcomes. Standard pharmacological and psychosocial interventions often demonstrate limited efficacy or delayed onset of action in oncological and palliative settings. Psilocybin-assisted therapy has recently emerged as a potential adjunctive approach for the treatment of depression, anxiety, and existential distress in patients with life-threatening cancer. This narrative review synthesizes current clinical and neurobiological evidence regarding the use of psilocybin as an adjunctive treatment in oncology. Randomized controlled trials, systematic reviews, and case reports indicate that psilocybin administered within a structured psychotherapeutic framework may produce rapid and sustained reductions in depressive symptoms and anxiety, including improvements in existential well-being. Mechanistic findings suggest involvement of serotonergic 5-HT2A receptor activation, large-scale brain network modulation, and enhanced neuroplasticity. When applied in controlled clinical settings with appropriate screening and psychological support, psilocybin demonstrates a favorable safety profile. Although current evidence is promising, limitations related to sample size and methodological heterogeneity require cautious interpretation. Further well-designed trials are necessary to determine long-term efficacy and optimal integration into comprehensive cancer and palliative care.